Primary Central Nervous System Lymphomatoid Granulomatosis: Systemic Review - Xiang, Yuanyuan; Liu, Cuicui; Xue, Yuan; Li, Shan; Sui, Yanling; Li, Jifeng; Sun, Qinjian; Liu, Xiaohui (Frontiers in Neurology, 2020)
Lymphomatoid granulomatosis (LYG) is an infrequent lymphoproliferative disease typically involves the lungs, but may also affect the central nervous system (CNS). Isolated CNS involvement is very rare and its clinicopathological features have not been fully elucidated. Here we systematically reviewed the English literature through PubMed to collect all relevant case reports and small case series with pathologically confirmed primary CNS-LYG. 29 relevant articles with 40 cases were included in this systemic review. In cases where T cells and B cells were compared, T cells were predominant in 19 (79.2%), and B cells were predominant in 5 (20.8%). The overall infection rate of EBV was 48.1% (13/27), among which the infection rate was 40.9% (9/22) in immunocompetent patients and 80% (4/5) in immunodeficient (HIV-infected) patients. Among the patients who underwent pathological grading, 35.7% (5/14) were at grade I, 42.9% (6/14) were at grade II and 21.4% were at grade III. In conclusion, primary CNS-LYG is closely related to EBV infection and some cases may be predominantly T cell phenotype. Surgical resection may be effective for mass-like lesions, although there is still a lack of standard therapeutic regimen. Accurate grading of lesions is essential for treatment selection and prognosis evaluation.